Kemampuan Pemecahan Masalah Matematika pada Materi Teorema Pythagoras ditinjau dari Gender Siswa - Irwana, Ira; Turmuzi, Muhammad; Novitasari, Dwi (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The purpose of this study was to describe the mathematical problem-solving abilities on the Pythagorean theorem material in terms of gender. This type of research is qualitative research with descriptive method. The research subjects consisted of 3 male students and 3 female students. The instruments used in this study were a problem-solving ability test, and interview guidelines. Data were selected from 6 subjects out of 30 students based on each category of mathematical problem-solving ability level for in-depth interviews. The results showed that the mathematical problem-solving abilities of male students were more dominant than female students. Students with high mathematical problem-solving ability category are male students who are able to fulfill all stages of problem solving ability indicators (1) understanding the problem, (2) devising a plan, (3) carrying out the plan, and (4) looking back. Students with moderate mathematical problem-solving ability category are male and female students who can only carry out three stages of problem-solving ability indicators (1) understanding the problem, (2) devising a plan, (3) carrying out the plan but have not been able to go through the looking back stage. Students with low mathematical problem-solving ability category are female students who are only able to carry out two stages of problem-solving ability indicators (1) understanding the problem and (2) devising a plan, but have not been able to go through the carrying out the plan and looking back stages.